Social Media Tik Tok in Islamic Perspective - Wandi Wandi (State Islamic Institute of Bone, Indonesia, 2020)
AbstractThe development of communication technology facilitate the community, for instance the social media Tik Tok. It can be a popular social media in community which is loved and used by various groups. Social media Tik Tok is a video sharing application that provides various interesting facilities of video and music effects, it can relieve stress, boredom and the users can also develop their talents and creativity. From this phenomenon researcher interested to overview Tik Tok from Islamic perspective. This study employed descriptive literature study. The results of the study clarified that Tik Tok on Islam's perpective is a good social media to be used to establish friendship, providing information and socialization and as entertainment. However, it also has negative impact including addiction in using Tik Tok, the close behavior on sex and pornography that can vitiate the morals for its users. Therefore, the Tik Tok users have to be wiser in using that social media. Keywords: Social media; Tik Tok Application; Islam.